Social interaction in the emergence of toddler's mealtime spoon use. Issue 8 (7th May 2020) - Nonaka, Tetsushi; Stoffregen, Thomas A.
Abstract: The use of a spoon for eating is among the important daily skills in early development. The article provides an analysis of how caregiver–toddler interactions guides the attention of toddlers who were first learning how to use a spoon to spoon‐related action opportunities that were relevant to the mealtime context. Our analysis revealed several related results. First, caregivers often manipulated objects on the table (i.e., food and dishes), and toddlers were more likely than chance to use their spoon to contact food immediately after watching these caregiver manipulations. Second, toddlers looked more often at the caregiver's hand than at their face. Third, toddlers tended to look at the caregiver's hand when the caregiver was manipulating objects on the table, and after these looks, toddlers were more likely than chance to contact food with their spoon. Finally, the toddlers' choices about when to look at the caregiver were influenced by their own behavior, as if they wanted to know how the caregiver would react to what they had done. We discuss these results in terms of the learning of socially promoted action opportunities for meal‐related spoon use.